Toeplitz operators in Segal-Bargmann spaces of vector-valued functions vector-valued functions - Cichoń, Dariusz; Shapiro, Harold S. (MATHEMATICA SCANDINAVICA, 2003)
We discuss new results concerning unbounded Toeplitz operators defined in Segal-Bargmann spaces of (vector-valued) functions, i.e. the space of all entire functions which are square summable with respect to the Gaussian measure in $C^n$. The problem of finding adjoints of analytic Toeplitz operators is solved in some cases. Closedness of the range of analytic Toeplitz operators is studied. We indicate an example of an entire function inducing a Toeplitz operator, for which the space of polynomials is not a core though it is contained in its domain.